PERANAN BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT DALAM PENANGGULANGAN TINDAK PIDANA DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Tri Nanda Putri; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Patrons bhayangkara Public Order and Safety hereinafter referred Bhabinkamtibmas is the police that one of its functions in terms of tackling crime. Based on the Police Regulation No. 3 of 2015 On Community Policing stated Bhabinkamtibmas is Bearer of Community Police in the Village / Sub. Marakya crime that occurred in the city of Pekanbaru like curanmor, nozzle, curas, persecution and more inseparable from the role Bhabinkamtibmas. Bhabinkamtibmas not optimal role in the prevention of criminal acts in the resort town Police Jurisdiction Pekanbaru mnyebabkan security and public order did not materialize. Therefore needed by Bhabinkamtibmas optimal role in the prevention of crime.The purpose of this thesis, namely: First, To know Bhabinkamtibmas Role in the prevention of criminal offenses in the jurisdiction of Police Pekanbaru. Secondly, To know Bhabinkamtibmas obstacle in the fight against criminal offenses in the jurisdiction of Police Pekanbaru. Third, to determine the constraints Bhabinkamtibmas efforts in the fight against criminal offenses in the jurisdiction of Police Pekanbaru.This type of research can be classified in this type of sociological research. The research location is Pekanbaru City Police. Source data used are primary data and secondary data. Data collection techniques are interviews, questionnaires and review of the literature using the deductive method of drawing conclusions from things that are common to the things that are special. From the research, there are three main things that can be inferred, first, Role Bhabinkamtibmas in the fight against criminal offenses in the jurisdiction of City Police Pekanbaru still not optimal demonstrated high crime rate that occurs, the task has not been thoroughly Bhabinkamtibmas reach people in villages. Second, Constraints Bhabinkamtibmas in the fight against criminal offenses in the jurisdiction of Police City of Pekanbaru, including personnel Bhabinkamtibmas limited, lack of infrastructure and facilities in the form of vehicles, Home Office is inadequate, the lack of technology (computer, machine print, Hanp Phone Office), lack of budget Bhabinkamtibmas operations, lack of ability Bhabinkamtibmas and not walk FKPM optimally. Third, efforts to Overcome Obstacles Bhabinkamtibmas in the fight against criminal offenses in the jurisdiction of Police Pekanbaru City include increasing the number of personnel Bhabinkamtibmas, additional infrastructure and facilities in the form of vehicles, Home Office adequate, technology (computer, machine print, Mobile Office), the addition of the operating budget Bhabinkamtibmas, increased ability Bhabinkamtibmas and coordination through FKPM optimally.Keywords: Role - Bhabinkamtibmas - Prevention - Criminal